Multiple roles for corticotropin releasing factor: acute and enduring effects of CRF on cocaine self-administration via interactions with mesolimbic circuitry. - Leonard, Michael. (Tufts University. Tisch Library., 2019)
Addiction can be characterized as a disorder of aberrant drug- or reward-seeking behavior. This pattern of behavior emerges, in part, from a dysfunction in how we perceive and anticipate the rewarding consequences of drug-associated contexts or cues. It is well known that stress experience contributes to addiction vulnerability, perhaps due to its profound effects on motivated behavior. The ability of stress to engage and modify mesolimbic dopamine circuits may underlie the motivational disturbances that are central to pathological drug use. Exposure to social stressors provokes CRF release into the VTA and terminal output regions in order to induce both transient, and persistent modulation of mesolimbic dopamine activity in rats. These enduring adaptations are associated with an intense cocaine-taking phenotype, which can be prevented by CRF receptor antagonists. The present studies examine the contributions of CRF to acute and enduring effects stress on cocaine self-administration. In Study 1, we test the extent to which CRF interactions within the VTA can directly reproduce excessive, binge-like cocaine consumption, in the absence of external stress experience. Further experiments explore the behavioral impact of stress or intra-VTA CRF infusions on cocaine reward valuation, in order to clarify the behavioral maladaptation that drives binge-like drug consumption. In Study 2 we narrow our focus to the behavioral and neurochemical interplay between CRF and dopamine within the nucleus accumbens core. We evaluate the acute impact of NAcC-CRF on instrumental responding for cocaine; and, in an additional set of experiments, we begin to characterize the conditions under which CRF modulates local dopamine transmission. Rats that experienced social defeat or received intra-VTA CRF microinfusions (50ng/side) both took significantly more cocaine than controls over a 24-hour unlimited-access 'binge', but showed divergent patterns of intake. Behavioral economic analysis revealed that an individual's demand for cocaine strongly predicts binge-like consumption, and that demand elasticity (i.e. α) is persistently augmented by intra-VTA CRF, but not by social defeat. The enduring effects of CRF on cocaine-taking were also prevented by intra-VTA pretreatment with CP376395 (500ng/side), but not Astressin-2B (1000ng/side). Acute microinfusion of CRF, on the other hand, dose-dependently increased responding during the fixed-interval link (FI5) of a heterogeneous chain schedule, but did not affect subsequent cocaine intake (FR1). These effects were CRF-R2-dependent, as CRF-potentiated responding was prevented by pretreatment with Astressin-2B (1000ng/side), but not CP376395 (500ng/side). When administered alone, Astressin-2B was also sufficient to attenuate cocaine-seeking responses. Parallel microdialysis studies revealed CRF is endogenously released into the NAcc during acute social defeat and, moreover, that perfusion of CRF into the NAcc is sufficient to elicit a robust increase in extracellular dopamine. The collective findings point to a role for CRF-R1 in the development of intense binge-like drug-taking behavior as a consequence of exaggerated cocaine valuation. Alternatively, CRF-R2 activation temporarily invigorates appetitive drug-seeking behavior via interactions with NAcc dopamine. Through discrete mechanisms CRF engages mesolimbic circuits to maladaptively strengthen behavior directed toward cocaine-consumption. Together, we characterize both acute, and enduring mechanisms by which stress may enhance vulnerability for pathological cocaine use.; Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Psychology.; Advisor: Klaus Miczek.; Committee: Jack Bergman, and Joe Debold.; Keyword: Neurosciences.